THE EFFECT OF ROLE PLAY TECHNIQUE ON THE SPEAKING ABILITY OF THE THIRD YEAR STUDENTS OF SMPN 14 PEKANBARU - Keumalahayati, Citra; Eliwarti, Eliwarti; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental study is aimed at finding out if there is a significant effect of role play technique on the speaking ability of the third year students of SMPN 14 Pekanbaru. The design of the study is one group pre-test-treatment-posttest design. There are 8 classes in the third year. As many as 37 students of class IX 3 in the first semester of academic year 2018/2019 are chosen as the sample by using cluster random sampling technique due to the particular class presents various characters of the whole classes like; academic achievement, the students’ learning seriousness toward English and the size of the classroom. The instrument of the test is in the form of acting from script. To collect the needed data the treatments using role play technique were conducted for six times. The students’ scores were analyzed by using SPSS (Statistical Package for the Social Sciences) version 23.00 for windows. The results of the data analysis show that the mean score of the pre-test is 51.24 and the mean score of the post-test is 60.42. It means that the value of t-test is higher than t-table (10.767>2.028) at 5% the significance level. Therefore, the alternative hyphotesis (H1) of this study is accepted. In other words, there is a significant effect of Role Play technique on the speaking ability of the third year students of SMPN 14 Pekanbaru. The implication of this finding is beneficial for the teachers in teaching and learning English especially in teaching speaking.Keywords: Effect, Role Play, Ability, Speaking.